Uma Análise in loco da degradação ambiental hídrica: o caso da microbacia hidrográfica do rio Peixe-Boi no estado do Pará - CARVALHO, André Cutrim (2022)
This article has as object of study a brief analysis of water environmental degradation in a defined section of the watershed Manatee River, which is housed within the territorial limits of Manatee County, State of Pará, from the perspective of the adoption of the watershed as a management unit. The methodology is based in the systemic analysis of water resources, as well as in obtaining data (bibliographies, photos and interviews) prevailing for the understanding and development of the theme presented. The main conclusion of this study is the lack of commitment of the government towards water issues in the State of Pará, particularly in Manatee County, which provided evidence of a recurrent and disturbing process water environmental degradation due to technical failure and professional local managers in materializing the guidelines of the State Water Resources Plan (PERH in Brazil), which creates a gap in the city's relationship with the state.